Body burden of pesticide residues vis-à-vis occurrence of reproductive disorders in dairy animals - RATNAKARAN, U; GHUMAN, S P S; BEDI, J S; GILL, J P S (The Indian Journal of Animal Sciences, 2014)
For assessing the association between body burden of pesticide residues and occurrence of reproductive disorders in dairy cattle and buffalo, random blood samples were collected from reproductively normal or abnormal bovines (190) reared in high pesticide usage (HPU) and low pesticide usage (LPU) area of Punjab state. Multiple pesticide residue analysis was done using gas chromatography (GC) and GC-mass spectrometry (GC- MS). Overall, about 16.8% bovines were detected positive for pesticide residues (56.1±62.1 ng/ml). The two most commonly detected pesticide residues in blood serum samples of bovines were DDT and its metabolites and chlorpyriphos. Serum pesticide residues were not different between the estrus cyclic and anestrus bovines. Compared to normal estrus cyclic or anestrus bovines, the proportion of bovines positive for pesticide residues as well as suffering from repeat breeding syndrome tended to be higher (24%) along with higher serum pesticide residues (70.1±82.8 ng/ ml). In contrast, the proportion of bovines positive for a pesticide residue and exhibiting pregnancy was very less (4%), and their serum pesticide residues was also low (11.8±0.5 ng/ml). In brief, these findings suggested that serum concentrations of pesticide residues may play a role in occurrence of reproductive disorders.